2013
DOI: 10.3897/compcytogen.v7i3.6126
|View full text |Cite
|
Sign up to set email alerts
|

Meiosis in rare males in parthenogenetic Cacopsylla myrtilli (Wagner, 1947) (Hemiptera, Psyllidae) populations from northern Europe

Abstract: For studying meiosis in males, large samples of Cacopsylla myrtilli (Wagner, 1947) (Hemiptera, Psyllidae) were collected in Norway, Sweden, Finland and northwest Russia. In addition to all-female populations, males were present in 10 out of 47 populations; still, all populations were highly female-biased, the proportion of males varying from 0.1% to 9.1%. These males are thus rare or so-called spanandric males. Males in northern Norway, Finland and northwest Russia showed normal chiasmate meiosis, while comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 31 publications
0
28
1
Order By: Relevance
“…1b). Interestingly, diploid females displayed chiasmate bivalents irrespective of the type of male meiosis, this being chiasmate in White Sea and Paltamo or achiasmate/asynaptic in Rindhovda (Nokkala et al 2013). This indicates that the gene carrying the mutation resulting in asynapsis in males is male specific in its function.…”
Section: Diploid Females and Female Meiosismentioning
confidence: 92%
See 3 more Smart Citations
“…1b). Interestingly, diploid females displayed chiasmate bivalents irrespective of the type of male meiosis, this being chiasmate in White Sea and Paltamo or achiasmate/asynaptic in Rindhovda (Nokkala et al 2013). This indicates that the gene carrying the mutation resulting in asynapsis in males is male specific in its function.…”
Section: Diploid Females and Female Meiosismentioning
confidence: 92%
“…Although it is tempting to think that diploids reproduce bisexually at Rindhovda, there is firm evidence to show this is not the case. Previously (Nokkala et al 2013), we showed that males at Rindhovda display achiasmate meiosis and are thus nonfunctional, producing only diploid sperms. Even if females produced haploid eggs, mating with males would result in triploid, not diploid offspring, Hence, diploid females and males must be produced in every generation by parthenogenetic females as reversals from triploidy by eliminating one haploid chromosome set.…”
Section: Diploid Females and Their Originmentioning
confidence: 98%
See 2 more Smart Citations
“…The psyllid life cycle comprises: the egg stage, five nymphal stages and sexually reproducing adults (Hodkinson, 1974). Parthenogenetic reproduction is possible but rare and it has been documented only in few psyllid species (Hodkinson, 2009;Nokkala et al, 2013). In the sexual reproduction phase, after mating and egg maturation, females oviposit in the edges or in the underside of the host plant leaves.…”
Section: Psyllids As Agricultural Pestsmentioning
confidence: 99%